Radiometric survey with Remotely Piloted Land Vehicle in Chemical, Biological, Radiological and Nuclear Defense operations - A. M. de Azevedo; J. L. Gonçalves; A. P. Salazar; D. D'O. Cardoso; P. V. Gonzales; V. A. V. Ferreira; W. V. Nunes (Brazilian Journal of Radiation Sciences, 2023)
This article addresses the development of a remotely piloted vehicle for the chemical, biological, radiological, and nuclear army defense system, able itself to perform radiometric surveys remotely favoring the process of local mapping and investigation of possible dispersions of radioactive materials in radiological and nuclear accidents and incidents. Tests were carried out to verify the efficiency of the developed prototype and it can be verified that the vehicle has a great applicability and optimizes the radiological protection process.